The Effect of Video-Based Learning on Students’ Learning Outcomes in Islamic Education: A Study of Prayer and Dhikr at SMP IT Mutiara - Muhammad Suheri; Mahariah (Darul Yasin Al Sys, 2026)
Students’ learning outcomes in Islamic Religious Education (PAI), particularly in ritual prayer (salat) and dhikr, were relatively low at SMP IT Mutiara. This condition was associated with conventional teaching methods that provided limited opportunities for active student engagement. This study evaluated changes in students’ PAI learning outcomes following the implementation of video-based learning. A quantitative pre-experimental method with a one-group pretest–posttest design was employed, involving 16 seventh-grade students. Data were collected through observations, tests, and documentation and analyzed using normality, homogeneity, and paired-samples t-tests in IBM SPSS Statistics 23. The findings demonstrated a substantial improvement in learning outcomes after the intervention. The mean score increased from 59.38 at pretest to 85.62 at posttest, representing a gain of 26.24 points. The paired-samples t-test confirmed that the difference was statistically significant (t = 5.885, p < 0.001). These results indicate that the implementation of video-based learning was associated with improved student achievement in PAI lessons on salat and dhikr. Video-based learning may therefore serve as an engaging, interactive, and contextual instructional medium for topics requiring conceptual understanding and visualization of religious practices. However, because the study employed a one-group design without a comparison group, the findings do not establish causality and should be confirmed through controlled studies with larger samples.